A Cooperative Path Planning Algorithm for Handling Robot. (November 2020) - Cai, Li; Zhu, XiaoLing; Li, Jingchuan
Abstract: Path planning is one of the core research fields of the handling robot, which has the characteristics of complexity and constraint. Ant colony algorithm is a search algorithm developed in recent years, which has good performance and development potential in solving many complex problems. In this paper, ant colony algorithm and workspace modeling are used to determine the optimal path for the global path search algorithm of the handling robot. The results of spatial modeling and software simulation show that the ant colony algorithm has advantages in the path planning of the handling robot. This path planning algorithm can provide the corresponding solutions for the search path problem of the complex robot.